Removing Barriers to Trade on Environmental Goods: An Appraisal - Gaëlle Balineau; Jaime de Melo (Fondation pour les études et recherches sur le développement international (FERDI), 2013)
This paper reviews the extent of reductions in tariffs in environmental goods (EGs) by countries participation in the negotiations mandated by a Doha Ministerial Decision in November 2001. Symptomatic of the cleavages across countries throughout the Round, little progress was achieved during the negotiations in defining an approach to a multilateral reduction in protection on EGs. Conflicting interests and differing perceptions on the benefits from increased trade in EGs was reflected in the different approaches proposed by members (request and offer, integrated project, list approach, hybrid approach).
Keywords: F18; Q56; 330